JOURNEY OF VERNACULAR ROOF TYPOLOGY IN SLAGI VILLAGE - Shofie, Athia; Prianto, Eddy (Journal of Architecture&ENVIRONMENT, 2025)
Vernacular architecture is identified as a form of architecture that evolves with the times. The concept of this architecture remains relevant because rural communities tend to build their homes based on longstanding traditions passed down through generations. However, changes in vernacular architecture can occur due to various factors, including adaptation to modern developments and residents' needs. In this article, the evolution of vernacular roof forms from the past to the present is analyzed, focusing on the vernacular roofs of houses in Slagi Village. Through a comparative study of old and new vernacular house roofs, the evolution of vernacular roof architecture is explored, and the factors influencing roof shape changes are investigated. Descriptive and comparative analysis approaches are used to review the differences in roof forms, and the cultural and environmental implications of these changes are understood. Findings show significant changes in vernacular roof forms from the past to the present, influenced by technological advancements and architectural trends. This article provides deep insights into the transformation of vernacular architecture and highlights the importance of preserving cultural heritage in the context of changing times. With a better understanding of the evolution of vernacular architecture, it is hoped to raise awareness of the importance of safeguarding and preserving cultural heritage for future generations.